(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of occupational stress among nurses working in the Intensive Care Unit (ICU) using the Expanded Nursing Stress Scale (ENSS) at Viet Duc University Hospital in 2024. Methods: A cross-sectional study was conducted among 130 ICU nurses. Results: The mean ENSS score was 108.81 ± 28.51. The average age of participants was 34.38 ± 6.44 years, and the majority were female nurses (66.2%). The most stressful domains were related to: patient and family-related issues; confronting patient death; inadequate emotional preparation; and conflicts with physicians. Nurses aged ≤30 years reported significantly higher levels of occupational stress compared with those older than 30 years. Conclusion: The findings highlight an urgent need for greater attention to the psychological and mental well-being of healthcare workers.